Quantitative analysis of behavioural phase difference in Locusta migratoria migratorioides (Reiche and Fairmaire, 1849) (Orthoptera, Acrididae) from the examination of spatial distribution patterns - (:unkn) unknown (My University, 2024)
The field of animal behaviour has often relied on tracking and recording the behaviour of a single individual. For example, for decades, gregarious locust behaviour research has used a standard assay that tracks the path of an individual in a cell, including how much time it spends next to an adjacent cell containing a group of stimulus locusts. However, this process can be time-consuming and impractical in lab and field settings. Here, we validate a complementary approach that uses spatial distribution patterns of a group of locusts in a circular arena to characterize the level of gregarious behaviour. We examined temporal variations in nearest neighbour distances as a criterion of attraction–repulsion and the successive changes of position of the individuals as a criterion of activity level. We used 3rd instar juveniles of the Migratory Locust, Locusta migratoria migratorioides (Reiche and Fairmaire1849), reared in isolated or crowded conditions. Locusts exhibit density-dependent plasticity, and crowd-rearing induces gregarious behaviour. As predicted, we found a larger nearest-neighbour distance between isolated-reared hoppers (indicating repulsion) than mass reared hoppers, which showed attraction to their conspecifics. Mass reared locusts walked greater distances, marking higher activity levels, which is another characteristic of gregarious locusts. These results indicate that this is an efficient and effective method of quantifying gregarious behaviour.
Keywords: African Research